2013
DOI: 10.1093/infdis/jit441
|View full text |Cite
|
Sign up to set email alerts
|

High Rates of Incident and Prevalent Anal Human Papillomavirus Infection Among Young Men Who Have Sex With Men

Abstract: Although the high prevalence of HPV among YMSM highlights the desirability of vaccinating all boys as a strategy to avert the morbidity of HPV infection, most YMSM appear to remain naive to either HPV-16 or -18 well into their sexual lives and would benefit from HPV immunization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
43
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 24 publications
7
43
1
1
Order By: Relevance
“…In contrast to the older population in the current study, other studies of anal HPV incidence have focused on young adult MSM [17][18][19]. These studies reported incidence rates for high-risk HPV ranging from 3.1 per 100 person-years for 94 young MSM (aged 16-30 years) recruited in Seattle [17] to 76.8 per 100 person-years [18].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In contrast to the older population in the current study, other studies of anal HPV incidence have focused on young adult MSM [17][18][19]. These studies reported incidence rates for high-risk HPV ranging from 3.1 per 100 person-years for 94 young MSM (aged 16-30 years) recruited in Seattle [17] to 76.8 per 100 person-years [18].…”
Section: Discussionmentioning
confidence: 77%
“…These studies reported incidence rates for high-risk HPV ranging from 3.1 per 100 person-years for 94 young MSM (aged 16-30 years) recruited in Seattle [17] to 76.8 per 100 person-years [18]. Among women, a study of 650 Hawaiian women with a median age of 40 years observed a 12-month incidence of high-risk anal HPV of 24% [20], which is similar to the estimate observed in the current study among MSOM (19%).…”
Section: Discussionmentioning
confidence: 99%
“…HPV-related infections have the potential to cause pre-cancerous lesions in the anal canal that may progress to anal cancer. Although most people will be exposed to HPV in their sexual lifetimes, certain high-risk groups including PLWH and MSM are at increased risk for developing HPV-related anal cancer (Glick et al, 2014). The current prevention options for sexually active people are limited.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of HPV is nearly universal within the MSM population and, as a result, aHSIL disproportionately affects MSM who have HIV (Glick, Feng, Popov, Koutsky, & Golden, 2014;Hessol, et al, 2009;Koutsky, 1997). In a meta-analysis by Machalek et al (2012, the prevalence of aHSIL in HIV-infected MSM proved by biopsy was 29% compared with 22% in HIV-uninfected MSM.…”
Section: Hpv Epidemiologymentioning
confidence: 99%
“…[12][13][14] Preliminary evidence has also shown that HPV may increase risk of HIV acquisition. 15 These costly and burdensome conditions are preventable, 16 yet no programs of screening for HPV infection are currently available to males.…”
mentioning
confidence: 99%